Adopsi IoT Pada Core Process Trucking di Indonesia Dengan Menggunakan TOGAF Framework - bayu Yasa Wedha; Hadri Helmi; Erick Dazki; Richardus Eko Indrajit (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Logistics costs in Indonesia are still relatively expensive due to the lack of infrastructure, technology, human resource capabilities, government logistics policies, natural disasters, and frequent illegal levies. Customers have not received information in real time. This can have an impact on customer satisfaction and delays in the payment process from customers. To answer these challenges, trucking business actors are required to innovate and improve the performance and utilization of their vehicles, especially by utilizing internet of things technology (IoT). The implementation of IoT technology in trucking companies requires enterprise architecture planning, so that the technology implemented is in accordance with business needs. This journal will discuss how to use IoT technology to support business goals and operational processes in the core process of trucking companies in Indonesia, as well as provide recommendations for enterprise architecture according to TOGAF that can be implemented in the core process of trucking business in Indonesia. Enterprise architecture recommendations are visualized through Archimate, so they can be easily understood and adapted by trucking businesses or the government.